Lattice Boltzmann method. - Chng, Joycelyn Pei Shi. (2009)
Lattice Boltzmann Method (LBM) computationally can be split into two steps process: advection and collision. Theoretically, since there are no floating point operations in the advection process, the execution of the advection scheme should be negligible compared to collision. However, in reality it takes about the same time as collision step which involves floating point operations. Thus, implementation of advection needs to be carefully designed for efficiency reason. In this report, three different advection algorithms are discussed and compared based on their advantages and disadvantages. Kida flow is also used to test the efficiency and accuracy of our D3Q15 model. The results are in good agreement with the qualitative data established by Shyam. Quantitative analysis of the data will be left for future work.